2020
DOI: 10.1002/wer.1468
|View full text |Cite
|
Sign up to set email alerts
|

Achieving single‐stage partial nitritation and anammox (PN/A) using a submerged dynamic membrane sequencing batch reactor (DM‐SBR)

Abstract: Single‐stage partial nitration and anammox (PN/A) process was achieved in a sequencing batch reactor (SBR) using a submerged dynamic membrane (DM) in this study. The reactor was stably operated for 200 days, and the nitrogen removal efficiency (NRE) was sustained at 70.3 ± 7.2% at a nitrogen loading rate (NLR) ranging from 0.1 to 0.3 kgNm−3 day−1 with a hydraulic retention time (HRT) of 24 hr. When the NLR was 0.2 kgN m−3day−1, the NRE achieved was high as 80% with a low concentration of dissolved oxygen (DO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Analysis of the data at the SPN/A stage revealed that with the higher NRE in each stage, the corresponding above ratio was nearly 0.11, which was compatible with the finding of Chen et al (2019). A previous study reported that the performance of the SPN/A system in a dynamic membrane SBR with intermittent aeration, at influent NH 4 + ‐N of 300.00 mg/L, the NRE reached 70.31 ± 7.20% (Yang et al, 2021). In this research, an SBR was used to start and create a steady operation of an SPN/A system and obtained high activity of AOB and anammox bacteria with a NRE reaching 77.11% under intermittent aeration mode.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Analysis of the data at the SPN/A stage revealed that with the higher NRE in each stage, the corresponding above ratio was nearly 0.11, which was compatible with the finding of Chen et al (2019). A previous study reported that the performance of the SPN/A system in a dynamic membrane SBR with intermittent aeration, at influent NH 4 + ‐N of 300.00 mg/L, the NRE reached 70.31 ± 7.20% (Yang et al, 2021). In this research, an SBR was used to start and create a steady operation of an SPN/A system and obtained high activity of AOB and anammox bacteria with a NRE reaching 77.11% under intermittent aeration mode.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it is necessary to develop more feasible strategies for the start-up of the SPN/A process. Previously, researchers found some strategies to inhibit NOB, such as manipulation of aeration duration (Li et al, 2021), increase of temperature (Malovanyy et al, 2015), increase of free ammonia (FA) concentration (Wang, Li, et al, 2020), as well as limitation of dissolved oxygen (DO) concentration (Yang et al, 2021). Moreover, the repetitive and alternating operations of the aeration system were an effective way to suppress NOB activity and achieve nitritation process stability (Miao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%